2018
DOI: 10.1371/journal.pone.0198160
|View full text |Cite
|
Sign up to set email alerts
|

Clinical inertia in basal insulin-treated patients with type 2 diabetes – Results from a retrospective database study in Japan (JDDM 43)

Abstract: AimsThis retrospective cohort study investigated whether clinical inertia, the failure to intensify treatment when required, exists in Japanese clinical practice, using the CoDiC® database. How and when patients with type 2 diabetes treated with basal insulin received treatment intensification was also described.Materials and methodsPatients with type 2 diabetes who initiated basal insulin between 2004 and 2011 were eligible for inclusion. Patients with an HbA1c ≥7.0% (≥53.0 mmol/mol) after 180 days of basal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…Moreover, because of the associated risk of hypoglycaemia and weight gain, 44,45 BB therapy is difficult for most people with T2D to maintain outside of hospitals without ongoing medical support, resulting in de‐escalation of therapy in many cases. In the JDDM 43 retrospective cohort study, among Japanese people with T2D who had intensified BI with BB or premixed therapy, mean HbA1c was 8.2% after 17 months 46 ; therefore, insulin intensification with such therapies is not sufficient to provide glycaemic control in many people with T2D.…”
Section: Demographics and Clinical Characteristics Of Type 2 Diabetesmentioning
confidence: 99%
“…Moreover, because of the associated risk of hypoglycaemia and weight gain, 44,45 BB therapy is difficult for most people with T2D to maintain outside of hospitals without ongoing medical support, resulting in de‐escalation of therapy in many cases. In the JDDM 43 retrospective cohort study, among Japanese people with T2D who had intensified BI with BB or premixed therapy, mean HbA1c was 8.2% after 17 months 46 ; therefore, insulin intensification with such therapies is not sufficient to provide glycaemic control in many people with T2D.…”
Section: Demographics and Clinical Characteristics Of Type 2 Diabetesmentioning
confidence: 99%
“…Independently of large regional variation, widespread delay of insulin initiation has been reported also in other Countries from Central and South-Eastern Europe [41,42]. Finally, a retrospective cohort study investigating whether clinical inertia existed also in Japanese clinical practice, demonstrated that the estimated probability of intensifying treatment during the 12 months after recording HbA1c ≥ 7.0% (≥ 53.0 mmol/mol) was only 22.8%, and 27.5% after 17 months, evidence of clinical inertia in basal insulin-treated patients with type 2 diabetes in Japan [43].…”
Section: Box 2-the Other Face Of Inertiamentioning
confidence: 99%
“…Percentage of therapy intensification in patients with HBA1c > 8% (addition of an oral hypoglycemic agent or dosage increase for an existing therapy or initiation of insulin treatment) [33,83] Percentage of therapy intensification in patients with HBA1c > 7% [84] Percentage of initiation of insulin treatment in patients with HBa1c > 9% [42] Average time elapsed between type 2 diabetes diagnosis and initiation of insulin treatment in patients with non-target HBa1c [42] Percentage of patients with HBa1c > 7% undergoing basal insulin treatment for 180 days and subjected to the intensification of insulin therapy [43] Difference between the percentage of outpatient visits in which sBP was higher than the target minus the percentage of outpatient visits in which a modification of anti-hypertensive treatment was implemented, either type or dose of treatment, divided by the number of eligible visits. The resulting value is multiplied by the average difference between sBP as measured in all visits and the target value of sBP [85] Percentage of patients with non-target levels of LDL cholesterol and treated with statins, divided by the total number of eligible patients [86] Time (days) elapsed before a therapeutic intervention subsequent to sub-optimal lab test results [87] Percentage of healthcare professionals who prescribe the initiation of insulin therapy to patients with type 2 diabetes and HbA1c at the recommended threshold of 7-7.9% [42] Number of patients without therapy intensification, divided by the total number of patients with HbA1c ≥ 7%, multiplied by 100 [52] Time spent with poor glycemic control (HbA1c 7%, > 7,5%, > 8%) in patients with type 2 diabetes treated with DPP-4i/SGLT-2i until the intensification of treatment with insulin/GLP-1RA [88] Percentage of patients lacking therapy intensification within 180 days from metformin failure [89] through a methodology equated with the use of outcome indicators (Table 3).…”
Section: Referencesmentioning
confidence: 99%
“…Basal or pre‐mix insulin, in combination with oral agents such as metformin, are established treatments for T2D in Japan . However, many patients fail to achieve adequate glycaemic control and, therefore, may be at higher risk of developing long‐term complications, possibly as a result of clinical inertia …”
Section: Introductionmentioning
confidence: 99%
“…7 However, many patients fail to achieve adequate glycaemic control and, therefore, may be at higher risk of developing long-term complications, 8 possibly as a result of clinical inertia. 9 Barriers to optimal initiation and titration of insulin can include the increased risk of hypoglycaemia and weight gain, as well as the burden of the number of injections necessary to titrate and administer complex insulin regimens that is experienced by patients. 10 To help overcome some of these barriers, combination therapy with basal insulin and a glucagon-like peptide-1 receptor agonist (GLP-1RA), administered as separate injections, has been recommended by the Japanese Diabetes Society following successful outcomes from recent global trials.…”
Section: Introductionmentioning
confidence: 99%